EFFECTIVENESS OF LEGAL PROTECTION FOR CONSUMERS OF DANGEROUS COSMETIC PRODUCTS IN BANDA ACEH BY THE FOOD AND DRUG SUPERVISORY AGENCY OF ACEH - Ami Dasria Asja; M.Syuib (JURISTA: Jurnal Hukum dan Keadilan, 2025)
Many unlicensed cosmetic products continue to circulate without official distribution permits and contain hazardous chemicals such as mercury, hydroquinone, and lead in the city of Banda Aceh. According to official data from the Food and Drug Supervisory Office (Badan Pengawasan Obat-obatan dan Makanan [BPOM]) Aceh, for the period from November 2023 to October 2024, 55 cosmetic products containing hazardous substances were identified and withdrawn from circulation. This paper aims to assess the effectiveness of the legal protection efforts implemented by BPOM Aceh in addressing the issue of harmful cosmetics for consumers. The research employs a juridical-empirical method with a sociological approach, involving in-depth interviews with five victims and discussions with BPOM officials. The findings indicate that although BPOM Aceh has carried out supervision at both the pre-market and post-market stages, including online monitoring or cyber patrol, the legal protection provided has not been entirely adequate. This is due to the generally low level of legal awareness among the public, where victims often do not understand their rights, are unfamiliar with proper complaint procedures, and rarely check BPOM registration numbers before purchasing products. Moreover, the sanctions imposed on business operators are considered insufficient to create a deterrent effect. Based on these findings, the study concludes that the legal protection system in Banda Aceh remains less than fully adequate and therefore requires strengthened public education initiatives, more rigorous law enforcement, and improved inter-agency collaboration to ensure consumer safety.